Sensors: Flexible and Stretchable 3ω Sensors for Thermal Characterization of Human Skin (Adv. Funct. Mater. 26/2017). (July 2017) - Tian, Limei; Li, Yuhang; Webb, Richard Chad; Krishnan, Siddharth; Bian, Zuguang; Song, Jizhou; Ning, Xin; Crawford, Kaitlyn; Kurniawan, Jonas; Bonifas, Andrew; Ma, Jun; Liu, Yuhao; et al.
Abstract : Yonggang Huang, John A. Rogers, and co‐workers report a flexible and stretchable sensor for the thermal characterization of human skin in article number1701282 . Based on the 3ω method, potential applications of the sensor could range from non‐invasive use to surgical tools, or even implantable devices.